2019
DOI: 10.1136/jmedgenet-2019-106324
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metastatic pheochromocytoma and paraganglioma in SDHx mutation carriers: a systematic review and updated meta-analysis

Abstract: BackgroundPheochromocytoma and paraganglioma (PPGL) are tumours that arise from chromaffin cells. Some genetic mutations influence PPGL, among which, those in genes encoding subunits of succinate dehydrogenase (SDHA, SDHB, SDHC and SDHD) and assembly factor (SDHAF2) are the most relevant. However, the risk of metastasis posed by these mutations is not reported except for SDHB and SDHD mutations. This study aimed to update the metastatic risks, considering prevalence and incidence of each SDHx mutation, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…To our knowledge, this is the first systematic study of a single tertiary centre cohort of 59 individuals with germline SDHX variants describing the associations between the genotype on the one hand and both the clinical and histopathological phenotype on the other. SDHB variants were the most frequent, which is in accordance with previous reports (9,10,12,18,21). Two patients were diagnosed with a variant in SDHA and four patients were diagnosed with SDHC variants, which corroborates previous findings that these are much less common (9,10,12,22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this is the first systematic study of a single tertiary centre cohort of 59 individuals with germline SDHX variants describing the associations between the genotype on the one hand and both the clinical and histopathological phenotype on the other. SDHB variants were the most frequent, which is in accordance with previous reports (9,10,12,18,21). Two patients were diagnosed with a variant in SDHA and four patients were diagnosed with SDHC variants, which corroborates previous findings that these are much less common (9,10,12,22).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, existing prognostic markers cannot fully predict PPGL behaviour ( 6 , 18 ), which is a clinical challenge. To our knowledge, there is no previous systematic study of the genotype–phenotype associations in patients with solely germline variants in SDHX genes.…”
Section: Introductionmentioning
confidence: 99%
“…Succinate dehydrogenase is an important tricarboxylic-acid-cycle-related enzyme in the mitochondria, and mutations to this enzyme frequently occur in cancer ( 43 , 44 ). It has also been reported that the mutation rate of SDHC was higher among the succinate dehydrogenase complex subunits in cancer ( 26 ). Therefore, when we showed that SDHC was downregulated in MQ-treated ESCC cells, we hypothesized that SDHC may play an important role in ESCC tumor growth.…”
Section: Discussionmentioning
confidence: 91%
“…Succinate dehydrogenase as a key component of the mitochondrial respiratory chain (RC) of all living organisms (22), SDH mutation frequently occurred in cancer (23)(24)(25). SDHC has a higher mutation rate compared with SDHD (26). Firstly, we tested the SDHC protein level in human ESCC tissues and found the protein level of SDHC was higher in ESCC tissues than normal tissues ( Figure 5A).…”
Section: Sdhc Is Highly Expressed In Escc Tissues and Knocking Sdhc Dmentioning
confidence: 99%
“…In PPGLs' patients, it is well established that the presence of inactivating germline mutations in the Metastatic Paragangliomas and Pheochromocytomas: An Epigenetic View DOI: http://dx.doi.org /10.5772/intechopen.96126 SDHB gene is the most important molecular predictor of malignancy. More than 40% of patients with metastatic PPGLs (especially extra-adrenal tumors) carry germline SDHB mutations [6,7]. Although mutations in other PPGL-predisposing genes, such as FH, SDHC, SDHD, SDHA, and TMEM127 have been found in some patients with metastatic PPGLs, these mutations account for only <5% of cases.…”
Section: Epigenetic and Sdh-deficiency: A Connection With Metastatic mentioning
confidence: 99%